2014
DOI: 10.1093/schbul/sbu093
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Abnormalities in Schizophrenia and Schizotypal Personality Disorder

Abstract: Prior diffusion tensor imaging (DTI) studies examining schizotypal personality disorder (SPD) and schizophrenia, separately have shown that compared with healthy controls (HCs), patients show frontotemporal white matter (WM) abnormalities. This is the first DTI study to directly compare WM tract coherence with tractography and fractional anisotropy (FA) across the schizophrenia spectrum in a large sample of demographically matched HCs (n = 55), medication-naive SPD patients (n = 49), and unmedicated/never-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 66 publications
6
36
0
2
Order By: Relevance
“…For both psychopathologies, cognitive empathy impairments have been previously highlighted (Montag et al, 2007;Shamay-Tsoory et al, 2007;Baron-Cohen et al, 2013;Smith et al, 2014) as well as abnormalities of the microstructural organization of the cingulate bundle (Pugliese et al, 2009;Travers et al, 2012;Reis Marques et al, 2014;Lener et al, 2014;Whitford et al, 2014). To the best of our knowledge, no work to date has been planned to directly rely empathy impairments in these pathologies with abnormal DTI parameters in the cingulum.…”
Section: Cognitive Empathy Cingulum and Default Mode Network Connectmentioning
confidence: 99%
“…For both psychopathologies, cognitive empathy impairments have been previously highlighted (Montag et al, 2007;Shamay-Tsoory et al, 2007;Baron-Cohen et al, 2013;Smith et al, 2014) as well as abnormalities of the microstructural organization of the cingulate bundle (Pugliese et al, 2009;Travers et al, 2012;Reis Marques et al, 2014;Lener et al, 2014;Whitford et al, 2014). To the best of our knowledge, no work to date has been planned to directly rely empathy impairments in these pathologies with abnormal DTI parameters in the cingulum.…”
Section: Cognitive Empathy Cingulum and Default Mode Network Connectmentioning
confidence: 99%
“…Several studies have reported connectivity issues between frontal and occipital cortices (Fornito et al, 2011;Liu et al, 2012;Cheng et al, 2015), including fractional anisotropy deficits of inferior and superior longitudinal fasciculus pathways (Lener et al, 2015;Prasad et al, 2015). Therefore, although from EEG recordings we can only indirectly infer the cortical sources underlying scalp recorded activity, the current findings of decreased alpha resonance in frontal regions may reflect resonance deficits particularly in the frontal cortex, perhaps mediated by thalamo-cortical abnormalities, in addition to dysfunction in connectivity between occipital and frontal cortices preventing alpha oscillations from reaching frontal regions.…”
Section: Potential Pathophysiological Mechanismsmentioning
confidence: 99%
“…Clinically, schizophrenia spectrum disorders are defined as a continuum ranging in severity from schizophrenia and schizotypal personality disorder to prototypical schizophreniarelated personality disorder, and schizophrenia-like symptoms [93,[112][113][114][115]. This might be one of the reasons why schizotypal personality disorder is rarely studied alone.…”
Section: Schizotypal Personality Disordermentioning
confidence: 99%
“…Lener et al [114] used the diffusion tensor imaging (DTI) technique to compare the white matter tract coherence across the schizophrenia spectrum. They found that schizophrenia patients showed lower fractional anisotropy in the temporal lobe and cingulum compared with both healthy volunteers and schizotypal personality disorder patients.…”
Section: Schizotypal Personality Disordermentioning
confidence: 99%
See 1 more Smart Citation